BOMCAR 7: Developing Board Game Card Media for Enhanced Grammar Learning Among Indonesian EFL Students - Aliyyah, Naily Samakhatal; Shofiyuddin, Muh. (Jurnal Paedagogy, 2025)
This study aims to develop and evaluate BOMCAR 7 (Board Game Card Media Tenses Adventure), a game-based learning tool designed to enhance grammar proficiency through interactive instruction. Using a one-group pretest-posttest design, the research investigates the effectiveness of board game card media among 30 tenth-grade students at a private Islamic senior high school in Jepara, Indonesia. The development followed the ADDIE model, incorporating needs analysis, expert validation, and field testing. The board game focused on simple present tense structures within the "Great Athletes" theme, aligning with Indonesia’s Merdeka Curriculum. Validation by experts, teachers, and students yielded high ratings (85.0%-91.6%), confirming pedagogical quality and classroom feasibility. Statistical analysis revealed significant learning improvements. Students’ grammar scores increased from pretest (M = 62.2, SD = 12.57) to posttest (M = 76.8, SD = 9.60), representing a 14.6-point gain with a large effect size (Cohen’s d = 3.11, p < 0.001). Both parametric and non-parametric analyses confirmed these robust results. Qualitative findings showed increased motivation, enhanced collaboration, and reduced anxiety. Classroom observations documented active engagement and sustained attention during game sessions. The findings demonstrate that board game card media effectively enhances grammar instruction in EFL contexts. BOMCAR 7 successfully transformed abstract grammatical concepts into engaging learning experiences while maintaining curricular alignment. These results contribute to game-based language learning evidence and provide practical guidance for educators seeking innovative grammar instruction methods.